Dermatology life quality index in thai male androgenetic alopecia patients attending dermatology outpatient clinic - Theetat Surawan (2022)
Background: Androgenetic alopecia (AGA), regarded as the most common cause of hair disorder with increased frequency and severity as patients become older, negatively affects patients’ self-image, activities of daily living, and quality of life. Objective: To assess the quality of life of Thai male AGA patients using the Thai-language Dermatology Life Quality Index (DLQI) questionnaire and evaluate the associations among AGA patients’ demographic data, clinical characteristics, severity of AGA, socioeconomic status, and their quality of life. Materials and Methods: The study design was a cross-sectional descriptive analysis. One hundred two male patients diagnosed as AGA were included in the present study. All patients were interviewed about their demographic data, clinical characteristics of the disease, and then asked to complete the Thai version of the DLQI questionnaires. Results: There were 102 patients with a mean (SD) age of 36.5 (12.25) years. The first presentation of AGA was between the age of 16 and 59 years with the mean (SD) age of 27.0 (12.5) years. Type III vertex of the Hamilton-Norwood classification of male pattern baldness was the most common presentation (52.0%). Eighty-five (83.3%) patients had a family history of AGA with the majority from fathers (69.4%). The mean (SD) of the total DLQI score was 5.24 (5.19). Differences between the groups of patients aged 30 years and below and aged above 30 years showed that the younger group had significantly higher mean total DLQI scores, 6 versus 3 (p=0.02). Conclusion: The DLQI score of male AGA patients in the present study indicates that the younger age group, 30 years and below, of male AGA patients is significantly associated with higher mean DLQI score suggesting more undesirable effect on patient’s quality of life. Also, most male AGA patients have a family history of AGA, from the paternal side.